The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1073/pnas.0811196106
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of replication machinery assembly as revealed by the DNA ligase–PCNA–DNA complex architecture

Abstract: The 3D structure of the ternary complex, consisting of DNA ligase, the proliferating cell nuclear antigen (PCNA) clamp, and DNA, was investigated by single-particle analysis. This report presents the structural view, where the crescent-shaped DNA ligase with 3 distinct domains surrounds the central DNA duplex, encircled by the closed PCNA ring, thus forming a double-layer structure with dual contacts between the 2 proteins. The relative orientations of the DNA ligase domains, which remarkably differ from those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
54
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 29 publications
10
54
0
1
Order By: Relevance
“…The fully assembled Okazakisome (Figures 2 and 3) exhibits features compatible with previous EM studies of related subassemblies (PCNA-Lig-DNA [5] and PCNA-Pol-DNA [12]). To glean insight into the mechanism by which PCNA co-ordinates three client proteins to process Okazaki fragments, we fitted each constituent of the assembly using Chimera, based on their volumes and shapes (Figure 3).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The fully assembled Okazakisome (Figures 2 and 3) exhibits features compatible with previous EM studies of related subassemblies (PCNA-Lig-DNA [5] and PCNA-Pol-DNA [12]). To glean insight into the mechanism by which PCNA co-ordinates three client proteins to process Okazaki fragments, we fitted each constituent of the assembly using Chimera, based on their volumes and shapes (Figure 3).…”
Section: Resultssupporting
confidence: 84%
“…This is analogous to what was shown in the crystallographic study of the SsoPCNA1/'2 dimer associated to Fen1 [17], where the conformation of the endonuclease recalls the Y-chain in 1UL1. We used the EM reconstructions for PCNA-LigI-DNA and PCNA-PolBI-DNA (maps EMDB-5220 and EMDB-1485 [5,12]) as probes to assign densities for PCNA-containing subcomplexes. To fit individual client proteins, we used the PDB codes: 1UL1 [16] and 2IZO [17] for the PCNA-Fen1 complex ( Figure 3B), 1S5J [18] for PolB ( Figure 3C) and 2HIV [19] for the ligase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because further extension of the DNA would sterically clash with the ring, such a large tilting angle appears unlikely in this case (41). EM analysis of PCNA/Pol-B/DNA and PCNA/ligase/DNA assemblies suggested that DNA was tilted by 13°and 16°, respectively (42,43). By contrast, in the replication factor C/ PCNA/DNA ternary assembly, the DNA axis was found to be nearly perpendicular to the PCNA ring (44).…”
Section: Structural Determinants Of Flexibility For the Ternary Assemmentioning
confidence: 89%
“…Pascal and coworkers suggested that the initial interaction of DNA ligase with PCNA occurs via its PIP box and upon PCNA binding, DNA ligase I undergoes a rearrangement to a closed‐ring conformation 16. The DNA‐binding domain (DBD) of HsDNAligI interacts with PCNA suggesting that the interaction of DNA ligase and PCNA is not dependent on the PIP box 17 and electron microscopy studies support the notion that DNA ligase and PCNA interact via a conserved protein surface 18. Despite the existence of a surface interaction between HsPCNA and HsDNAligI, the effect of this interaction on the enzymatic activity of human DNA ligase is not as clear.…”
mentioning
confidence: 95%